Low ligand field strength ion (I−) mediated 1D inorganic material MoI3: Synthesis and application to photo-detectors - Choi, Kyung Hwan; Oh, Seungbae; Chae, Sudong; Jeong, Byung Joo; Kim, Bum Jun; Jeon, Jiho; Lee, Sang Hoon; Yoon, Sang Ok; Woo, Chaeheon; Dong, Xue; Ghulam, Asghar; Lim, Changmo; et al. (Journal of Alloys and Compounds, 2021)
A new type of 1D inorganic material, MoI3, which can be separated into individual 1D chains, was synthesized through a vapor transport reaction between molybdenum and iodine. High-purity and centimeter-scale large MoI3 crystals were obtained by controlling the growth temperature and the stoichiometric ratio between molybdenum and iodine. Their semiconductor characteristics were confirmed by measuring the electrical conductivity as a function of temperature (conductivity increased with increased temperature across the range −70 to 30 °C). Furthermore, it was confirmed that MoI3 with a 1.27 eV band gap can be separated to a few nanometer scale through mechanical and chemical exfoliation methods and can be used as a photodetector in the near IR (less than 1000 nm)-to-visible light region. This novel 1D material is expected to play an important role in the development of additional low-dimensional materials and in advanced nano-optoelectronic devices.
Keywords: Chemical exfoliations; Electrical conductivity; Increased temperature; Inorganic materials; Low-dimensional materials; Stoichiometric ratio; Vapor-transport reaction; Visible light region; 1D inorganic materials; Mechanical exfoliation; MoI3; Photodetectors